Three-dimensional numerical modelling of multi-layered shell structures using two-dimensional plane mesh. (November 2020) - Jaśkowiec, J.; Stankiewicz, A.; Pluciński, P.
Highlights: The new method for 3D numerical modelling of multi-layered curved shells is proposed. The modelling is performed with exact geometry description. For calculations only 2D mesh is applied. The method is called FEM23: 2D FEM for 3D analysis. Examples are presented in which shells are composed with thick and thin layers. Abstract: The article presents a full three-dimensional (3D) numerical analysis of curved laminated shell structures using only a two-dimensional (2D) planar finite element mesh. The applied numerical method is called FEM23, which stands for the 2D finite element method for a full 3D analysis. FEM23 makes it possible to perform a numerical analysis of a multi-layered shell, utilising a numerical model based on a 2D finite element mesh. FEM23 ensures exact shell geometry since a pure mathematical description of a geometry is applied in the numerical model. Examples provided in the following paper prove FEM23 to be accurate and flexible. They involve the analysis of a special laminated structure - laminated glass, which comprises of glass panes bonded by thin polymer films. A full 3D description is provided for the glass panes as well as polymer films, even though the film thickness is over ten times smaller than the glass layers. The results are verified by the analytical solution and those obtained by standard 3D FEM. A unique post-processing procedure developed specially for FEM23 enables visualisation of the full 3D results.